Blocking effects in irreversible adsorption of linear macromolecules - Shelke, Pradip B.; Banpurkar, Arun G.; Ogale, S. B.; Limaye, A. V. (Surface Science, 2007)
{A new variant of random sequential adsorption (RSA), namely random sequential ballistic adsorption (RSBA), is proposed to explore the possible role of blocking effects in the adsorption dynamics of ballistically arriving objects. These objects upon adsorption can protrude outside the substrate and in turn can obstruct and hence reject the adsorption of newly arriving objects. Adsorption of linear macromolecules (modeled as infinitesimally thin needles), on a two-dimensional continuum substrate is studied using RSBA model. It is shown analytically that in late time regime, the number n(t) of adsorbed objects at time t follows a power law n(t) similar to t(alpha), as in RSA, but with a different exponent
Keywords: Adsorption; adsorption kinetics; Monte Carlo simulations; random sequential adsorption (RSA)